Multidimensional Scale of Attitudes Towards People with Disabilities - testing the psychometric properties of the Polish version - Ewa Domagała-Zyśk; Stanisława Byra (Studia z Teorii Wychowania)
Attitudes toward people with disabilities are a dynamic phenomenon, dependent on a number of legal, social and individual factors. In recent years, they have been shaped in Poland mainly by legislative changes related to the Convention on the Rights of Persons with Disabilities and the resulting national legislation, the introduction of the model of inclusive education, and social transformations through which diversity in terms of health and the (dis)abilities) one possesses is understood as a common experience, rather than a reason for isolation and rejection. The new paradigm of perceiving disability requires the use of new methods of studying contemporary phenomena, including attitudes toward people with disabilities. The purpose of this text is to present the process of adaptation to Polish conditions and proven psychometric properties of the Multidimensional Scale of Attitudes Toward People with Disabilities by L. Findler, N. Vilchinsky and S. Werner (2007). MAS-POL has satisfactory reliability ratings, both for the version targeting people with disabilities in general and those with motor, intellectual and sensory disabilities. The data obtained with this tool can expand existing analyses of attitudes toward people with disabilities, based on the more elaborate and complex structure of the phenomenon. It includes separate versions for measuring attitudes toward people experiencing different but most representative types of disabilities. Analysis of the tool's properties indicates that it can be a useful tool in contemporary research in the field of disability.